The Banality of Evil in Reiner Braun, Bertholdt Hoover, and Annie Leonhart's Actions in the Anime Attack on Titan - Nurani Permatasari (Universitas Airlangga, 2026)
This study aims to examine the representation of the banality of evil in the actions of Reiner Braun, Bertholdt Hoover, and Annie Leonhart in the anime Attack on Titan. Their actions against the people of Paradis cause them to be viewed as enemies of humanity. However, it was eventually revealed that their crimes are not driven by personal motives, but are related to Marley’s ideological system, which shapes their way of thinking and actions. Therefore, Hannah Arendt’s concept of the banality of evil is used as the analytical framework in this study. This research uses a qualitative method with a descriptive-analytical approach. The data were collected through note-taking techniques on dialogues and scenes in Attack on Titan and analyzed using interactive analysis. The results show that the banality of evil is represented through the characters’ failure to listen to their conscience, blind obedience to duty, and Marley’s ideological influence.